The Relevance of The Madrasah Diniah Takmiliyah Curriculum to Islamic Religious Education - Lutfia, Maya; Suharto, Yusuf; Srinio, Fuad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This article aims to describe the implementation of the Diniah curriculum in developing student character. The research method that has been used is qualitative with a case study approach. The reason this research was conducted is as evidence that the Diniah Takmiliah curriculum is still relevant to the current situation. The method of data collection with interviews, observation, and documentation. The determination of informants in this study is like a snowball from one informant to another so as to get maximum data. The findings of the article will provide a study of the relevance of the Diniah Takmiliyah Madrasah curriculum developed with Islamic Religious Education. study). One solution that can be done to overcome the problem of moral degradation is to optimize Islamic religious education for students. But in reality, the learning hours of Islamic religious education in public schools are very lacking. Given the importance of understanding Islamic religious education, SDIT Samawi takes a solution to the problem by implementing the Madrasah Diniah curriculum as a form of Curriculum Development.